First case of fungemia caused by a rare and pan-echinocandin resistant yeast Sporopachydermia lactativora in China - Qiushi Zheng; Shuzhen Xiao; Lingyu Ji; Jian Bing; Bing Li; Lizhong Han; Haiqing Chu; Guanghua Huang (Mycology)
The cactophilic yeasts, Sporopachydermia species, are intrinsic resistance to echinocandins. We report the first case of fungemia caused by S. lactativora in China. Sporopachydermia lactativora could colonise and infect multiple animal tissues and could represent a new emerging fungal pathogen of humans and should not be ignored in clinical settings.